Strategi Pemasaran Sayuran Hidroponik (Studi Kasus CV Spirit Wira Utama Tangerang Selatan) - Alfi Sabrina; Wagiono Wagiono; Suhaeni Suhaeni (Jurnal Ilmiah Wahana Pendidikan, 2022)
CV Spirit Wira Utama is a large company that produces hydroponic vegetables in the city of South Tangerang. Increased public awareness of healthy consumption patterns provides a great opportunity for CV Spirit Wira Utama. However, there are obstacles faced by company, including the company losing market segments in cafes and restaurants because it is not able to meet the demand in these segments and more similar companies are using social media as a tool for their branding and using the market. The purpose of this research is to examine the company’s internal and external factors to find a marketing strategy that can be recommended for the company. This study uses descriptive methods with qualitative and quantitative approaches to collect primary and secondary data. The sampling method used a purposive sampling technique with the number of respondents as many as seven people. The data analysis used was IFAS EFAS analysis, SWOT analysis, and QSPM analysis. The result of the QSPM research show that the strategy is “Building a brand identity by utilizing the development of technology and information by human resources who can be social media well” with score of 6.30.” and the strategy that has smallest score is ” inviting partners to increase vegetable variants by utilizing technology and information with a value of 5.17”